2001
DOI: 10.1039/b007136f
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation and characterisation of a new βIII­phase in Zr­doped Bi2O3

Abstract: The solid state system Bi 2 O 3 :ZrO 2 has been investigated up to 28 mol% ZrO 2 using X-ray and neutron powder diffraction, ac impedance spectroscopy and differential thermal analysis. X-Ray powder diffraction has shown that a solid solution is formed with general composition Bi 22x Zr x O 3zx/2 (0.05¡x¡0.17) for samples calcined at 850 ‡C. Members of the solid solution adopt a new b-Bi 2 O 3 type structure termed b III , which is closely related to Pb 2 F 2 O. The defect structure of a sample of composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 22 publications
(26 reference statements)
2
28
1
Order By: Relevance
“…This type of variation may be due to transformation of m-Bi 2 O 3 to δ-and β III -Bi 2 O 3 because of oxygen deficiency [10]. This type of transition has been reported above 700°C due to δ-β III polymorphs of Bi 1.33 Zr 0.67 O 3-δ phase [8,9]. Interestingly, the present samples also show phase transition, which is lower than earlier reported values.…”
Section: Resultscontrasting
confidence: 80%
See 2 more Smart Citations
“…This type of variation may be due to transformation of m-Bi 2 O 3 to δ-and β III -Bi 2 O 3 because of oxygen deficiency [10]. This type of transition has been reported above 700°C due to δ-β III polymorphs of Bi 1.33 Zr 0.67 O 3-δ phase [8,9]. Interestingly, the present samples also show phase transition, which is lower than earlier reported values.…”
Section: Resultscontrasting
confidence: 80%
“…Abraham et al [9] has suggested that solid solution limit for Bi 2-x Zr x O 3+x/2 system is x=0.17. On the other hand, very few studies have been reported in literature on Bi-doped ZrO 2 system [11].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The solubility of ZrO 2 monotonically decreases with increasing temperature so that deficient fluorite phases are completely decomposed at 750°ë to form ZrO 2 phases and the Bi 1.84 Zr 0.16 O 3.08 solid solution with a β-Bi 2 O 3 structure [7]. Analogous results were obtained in [8], where the existence of a series of Bi 2 -x Zr x O 3 + x/2 solid solutions (0.05 ≤ x ≤ 0.17) with a deficient fluorite structure and a melting point at 860°ë was found. It is worth noting that no solid solutions were observed in the ZrO 2 -CuO system in the temperature range we studied [9].…”
supporting
confidence: 61%
“…Since ZrO 2 exhibits good toughness and strength, the properties of ZrO 2 combined with the high conductivity of mBi 2 O 3 make it a superior oxygen ionic-conducting electrolyte [10]. In this system, the formations of various phases have been reported with changing processing condition [9,[11][12][13][14][15][16][17][18][19]. Recently, our group has also synthesized (100−x) ZrO 2 (x) Bi 2 O 3 (x05, 10, 15) system which showed good ionic conductivity [13].…”
Section: Introductionmentioning
confidence: 99%